Analisis Dampak Visual Appeal, Scarcity Message, Flash Sale, dan FOMO terhadap Impulsive Buying Produk Fashion pada Live Streaming TikTok Shop - Diva Fahsya Ardana; Usep Suhud; Ivan Putranto (Indo Publishing, 2026)
This study aims to analyze the impact of visual appeal, scarcity message, flash sale, and fear of missing out (FoMO) on impulsive buying of fashion products on TikTok Shop live streaming. The rapid growth of social commerce in Indonesia, particularly TikTok Shop, has transformed consumer shopping behavior, creating a more interactive and emotionally engaging shopping experience. This research employs a quantitative approach with a survey method using a questionnaire distributed to 175 respondents selected through purposive sampling. Respondents are Generation Z consumers (aged 18-28 years) residing in DKI Jakarta who have made impulsive purchases of fashion products on TikTok Shop live streaming at least three times in the past six months. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS software. The results indicate that scarcity message has a positive and significant effect on FoMO and impulsive buying. Flash sale has a positive and significant effect on FoMO, but does not have a significant effect on impulsive buying. Visual appeal does not have a significant effect on either FoMO or impulsive buying. FoMO has a very strong positive and significant effect on impulsive buying, with the highest critical ratio value of 4.651. These findings provide important implications for business actors in formulating digital marketing strategies, particularly in optimizing scarcity messages and creating FoMO to drive impulse purchases on live streaming platforms.